Pengaruh Tipe Kandang (Closed House dan Open House) dan Umur Ayam terhadap Tingkat Keuntungan Usaha Ayam Petelur - Agung, Fajar Agung; Haryuni, Nining; Lestariningsih, Lestariningsih (Universitas Islam Kadiri, 2024)
This study aimed to determine the effect of the type of cage and the age of the chickens on the profits of the laying hens business. The research was conducted from January to March 2022 at Buana Intan Sejati Farm, which is located in Kawedusan Village, Ponggok District, Blitar Regency. This study used 2000 laying hens using a 2x5 factorial completely randomized design (CRD). The first factor is the type of cage (K) which in this study used a close house type cage and an open house type cage. The second factor is the age of the chicken (U) which consists of 3 types of age, namely 33, 50 and 79 weeks. The results of statistical analysis showed that the type of cage gave a very significant effect (p<0.01) on production costs, revenues, profits and R/C; chicken age has a very significant effect (p<0.01) on revenue, profit and R/C; and the interaction between the two factors has a very significant effect (p<0.01) on revenue, profits and R/C. The conclusion of this study is that the type of cage and the age of the chickens have an effect on the profits of laying hens. The best interaction was found in close house cages and 33 weeks old chickens with a profit of IDR. 10,319,700,-/1000 heads/month and the R/C value is 1.3477